Implementasi Bantuan Sosial Di Indonesia Dalam Kerangka Sustainable Development Goals - Amrie Firmansyah; Dewi Darmastuti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2026)
This study examines the implementation of social assistance in Indonesia within the framework of the Sustainable Development Goals (SDGs) using audit-based evidence from the Semester II Summary of Audit Results (Ikhtisar Hasil Pemeriksaan Semester II/IHPS) for the period 2020-2024. A qualitative content analysis approach is employed to systematically identify recurring patterns of findings related to the implementation of social assistance programs. The analysis reveals persistent structural issues, including the quality and governance of beneficiary databases, targeting inaccuracies, suboptimal distribution of assistance, weaknesses in data control and updating mechanisms, limited integration of beneficiary data across programs, and deficiencies in validation and verification processes in education-related social assistance. These patterns indicate that challenges in social assistance implementation extend beyond policy design and span the entire policy implementation cycle. From a sustainability perspective, the identified issues are closely linked to efforts to reduce poverty, mitigate inequality, ensure inclusive access to education, and strengthen effective and accountable public institutions, as articulated in the SDGs. By relying exclusively on official audit documents as the data source, this study contributes to the literature by offering an institutional- and governance-oriented understanding of social assistance implementation grounded in systematic audit evidence rather than program-level performance evaluation. The findings underscore the importance of strengthening administrative capacity and institutional coordination to sustain social protection policies.